Perinatal outcome of neonates born to COVID SARS-CoV-2 positive mothers: a comparative study - Narayanappa Doddaiah; Shrisagar Rattehalli Ashwathnarayana; Sujatha Mysore Srikantha; Mounika Pydipally (International Journal of Contemporary Pediatrics, 2023)
Background: The entire world is experiencing a difficult scenario because of COVID-19 infection caused by severe acute respiratory syndrome coronavirus 2 (SARS‑CoV‑2). It is imperative to have comprehensive information on how COVID-19 affects pregnancy-related outcomes when compared to outcomes in uninfected pregnant women. Methods: Neonates born to SARS-CoV-2 positive mothers were included in the case group (n=127) and neonates born to SARS-CoV-2 negative mothers were included in the control group (n=127) in this prospective comparative study. In both groups, the mothers were matched for age, body mass index (BMI), morbidities, and parity. Neonatal morbidity and mortality in both groups were examined after neonates were monitored for 7 days after delivery. Results: Neonatal morbidity was more among neonates born to COVID positive mothers (p<0.05) but mortality did not show any significant difference. There was statistically significant difference in gestation and birth weight among cases and controls. No neonate born to COVID positive mother was tested positive for COVID by reverse transcriptase-polymerase chain reaction (RT-PCR). Mean APGAR score at 1min was less among neonates born to COVID positive mothers but at 5 minutes it was almost similar among both groups. Conclusions: According to the study’s findings, maternal COVID-19 infection significantly affects perinatal outcomes, neonatal morbidity, birth weight, and neonate gestational age.